Teaching Simple Past Tense Using Numbered Head Together (NHT) Strategy to Teenagers - Nur Afifa; Hilal Mahmud; Muhammad Iksan (Sekolah Tinggi Agama Islam Negeri Majene, 2021)
This paper is intended to find out the effectiveness of Numbered Head Together (NHT) strategy in teaching Simple Past Tense to Teenagers. This study is experimental study which applied the pre-experimental design in one group pre-test and post-test design. The writer collected data by giving pre-test and post-test which are formulated in multiple-choice items contained 10 items. The data collected through pre-test and post-test which were firstly tabulated and analyzed in percentage. The sample of the research was the students from different high school in Masamba categorized as a teenager aged 15-16 years old consisting of 10 students. This study revealed that the use of numbered head together strategy is effective in teaching simple past tense for teenagers. It is proved by the result of the data indicating that there was a significant difference between the pre-test and post-test. The mean score in the pre-test was 39,00 and the mean score in the post-test was 82,00. The value of t0 (tcount) = 7,435, the value of tt (ttable) = 1,833 at the level of significance 5% (0,05) with degree of freedom (df) = 9. Based on the result, t0 (tcount) was higher than tt (ttable), it means that the numbered head together strategy is effective in teaching simple past tense to teenagers.